1993
DOI: 10.1111/j.1365-2826.1993.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin‐Induced Growth Hormone Secretion in Conscious Rats: Evidence for a Possible Involvement of Somatostatin

Abstract: Intracerebroventricular administration of galanin (GAL) potently evoked growth hormone (GH) secretion in conscious male rats. Pretreatments with neostigmine and cysteamine blunted the GAL-induced GH secretion. Pretreatment of animals with a specific anti-somatostatin serum significantly inhibited the GAL-induced GH secretion. On the contrary, GH-releasing hormone-induced GH secretion was significantly enhanced with cysteamine and anti-somatostatin serum. These results suggest that somatostatin is involved in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
1
5
1
Order By: Relevance
“…In addition, it has been suggested that SRIF is not involved in ghrelin action [9,15,34], consistent with the present results. Although the inhibition of SRIF release by galanin was reported [42], we could not confirm it in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…In addition, it has been suggested that SRIF is not involved in ghrelin action [9,15,34], consistent with the present results. Although the inhibition of SRIF release by galanin was reported [42], we could not confirm it in this study.…”
Section: Discussioncontrasting
confidence: 78%
“…The expression of GAL in the ARC was similar in the ad lib and food-restricted animals. Evidence suggests that the effects of GAL on the secretion of GH involve SRIF-ergic inhibition (Loche et al 1990, Tanoh et al 1993 and GAL cells in the ARC project to the SRIF neurons in the PeVN (Liposits et al 1993). It is likely, therefore, that any effect on the GAL system may manifest as changes in the levels of SRIF in the PeVN and our results for the rPeVN are consistent with this.…”
Section: Rapid Communication R3supporting
confidence: 81%
“…In man, rat, porcine and human galanin stimulate basal GH secretion (3,4,29,30) as well as the somatotrope response to GHRH (5) and arginine (7). Based on animal (2,(31)(32)(33)(34)(35) and human (5,6,8,36) studies, the mechanisms underlying the GH-releasing effect of galanin seem to involve both GHRH-and somatostatin-mediated actions. However, a direct action of galanin on somatotrope cells cannot be ruled out (37,38).…”
Section: Discussionmentioning
confidence: 96%